Factors affecting the quality of life in pregnant women with diabetes: the mediating effect of illnesses acceptance - Azita Fathnezhad-Kazemi; Zahra Seifinadergoli; Mohaddeseh Ahmadi (BMC, 2024)
Abstract Introduction Gestational diabetes, as a disorder of carbohydrate metabolism, is considered one of the most common metabolic complications in pregnancy. The diagnosis of diabetes in pregnancy leads to changes in lifestyle, and the treatments employed can affect various aspects of pregnant women's lives, including their quality of life. The present study aimed to investigate the relationship between self-efficacy and the mediating effect of illness acceptance on the quality of life in pregnant women diagnosed with diabetes during pregnancy. Materials and methods This cross-sectional study was conducted on 240 pregnant women diagnosed with diabetes who were selected by convenience sampling method. Quality of life tools (SF12), the Acceptance of Illness Scale (AIS), and the Sherer self-efficacy scale were used to collect data. Results The mean (SD) of quality of life, self-efficacy, and disease acceptance were 57.36 (6.63), 51.75 (7.44), and 29.07 (7.69), respectively. In the single-variable regression analysis, self-efficacy and disease acceptance variables could predict 20.6% (β = 0.457, P < 0.001) and 14.4% (β = 0.385, P < 0.001) of the variations in quality of life, respectively. In the multiple regression model, by entering the two main variables (self-efficacy and Acceptance of Illness), demographic characteristics, three disease knowledge variables, health status from an individual perspective, and type of treatment, the variables could explain 25% of the changes of the quality of life (R2 adj 0.25, P < 0.001=). Income status and self-efficacy had the highest impact among the variables. According to the results of path analysis, the total effect of self-efficacy on the quality of life of pregnant women with diabetes was 0.711. Conclusion The overall quality of life in women with diabetes was moderate, and self-efficacy, illness acceptance, and income status were predictors of overall quality of life. Self-efficacy can influence the quality of life by affecting disease acceptance. The findings highlight the importance of designing educational programs and providing midwifery services to increase self-efficacy and illness acceptance to improve the quality of life of pregnant women with diabetes.